No Morphological Markers, No Problem: ERP Study Reveals Semantic Contribution to Distinct Neural Substrates Between Noun and Verb Processing in Online Sentence Comprehension - Feng, Jun; Gong, Tao; Shuai, Lan; Wu, Yicheng (Frontiers in Neuroscience, 2019)
Neural mechanisms behind noun and verb processing during the course of language comprehension are ubiquitously separate, yet it remains highly controversial as to which factor, syntax or semantics, should be responsible for this separation. This paper conducted an event-related potential (ERP), sentence comprehension experiment as an attempt to resolve this issue. The experiment used Chinese sentences in the configuration of noun phrase + 没 (“not/no”) + noun/verb/noun-verb-ambiguous-word, which excluded grammatical or syntactic factors that could hint at the lexical categories of sentence-final target words. Results showed significantly distinct ERP components of P200, N400 and P600 between noun and verb processing in native speakers, indicating that semantic factors are essential for the differentiated neural mechanisms behind noun and verb processing. Distinct P200, N400 and P600 also manifested between noun and noun-verb-ambiguous-word processing, but not between verb and noun-verb-ambiguous-word processing. This suggests that lacking clues on lexical category renders the dynamic properties of the ambiguous words more salient than the static properties, thus causing interpretation of such words more likely as verbs. This further elaborates the crucial role of semantic factors in noun and verb processing.